The influence of financial literacy, financial technology, financial attitudes, and financial self-efficacy on the financial behavior of Generation Z - Marselien, Lusiana Aryanti; Yola Andesta Valenty (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the influence of financial literacy, financial technology, financial attitude, and financial self-efficacy on financial behavior among Generation Z in Jakarta. The population in this study is Generation Z residing in Jakarta with a total population of 2,678,252 people. The sampling technique used the Slovin formula with a margin of error of 10%,resulting in data from 166 respondents via a questionnaire. The data was analyzed using the partial least squares structuralequation modeling (PLS-SEM) method with the assistance of SmartPLS 3.0 software. The results of the study indicate that all four independent variables have a positive and significant influence on financial behavior.